Behaviour change interventions for the management of Raynaud's phenomenon: a systematic literature review. Issue 12 (14th December 2018) - Daniels, Jo; Pauling, John D; Eccleston, Christopher
Abstract : Objectives: Raynaud's phenomenon (RP) is a significant cause of morbidity. Vasodilator medications cause unwanted adverse effects, with behavioural and lifestyle changes forming the mainstay of self-management; this is difficult to implement successfully. The objectives of this study were to evaluate the efficacy of behaviour change interventions for RP and identify learning points for future treatment development. Design: Systematic literature review and narrative synthesis of findings. Data sources: EMBASE, MEDLINE, Cochrane and PsycINFO were searched for eligible studies on 22 August 2017. Eligibility criteria: Randomised controlled trials (RCTs) of behaviour change interventions with at least one control comparator arm. Data extraction and synthesis: Study selection, data extraction and risk of bias were assessed independently by two reviewers, reaching consensus with a third when necessary. Primary outcomes of interest included severity/impact, frequency and duration of RP episodes, pain, disability, adverse events and study withdrawal. Results: Of 638 articles retrieved, eight studies fulfilled criteria for inclusion. Biofeedback was the active behaviour change treatment arm for seven studies, with one study reporting a behavioural intervention. Studies were published 1978–2002; six were USA-based studies, one German and one Swedish. Using Cochrane Risk of Bias assessment, studies were assessed to be overall at high risk of bias, with the exception of one large RCT. The total sample included 495 participants (study median=29), with a median age of 39.5 years and preponderance towards females (73%). Five studies reported significant effects in primary outcomes of interest; however, due to missing data, relative efficacy of interventions could not be reliably assessed. Conclusions: There is no evidence to support or refute claims of the efficacy of behaviour change interventions for the management of RP. There remains a strong case for developing and testing behaviour change interventions that focus on self-management; however, theoretical development and advancement in trial quality is imperative to underpin future work. PROSPERO registration number: CRD42017049643.